Capgras syndrome, an interesting but rare phenomenon in Psychiatry: A case series - Arghya Halder; Sagarika Ray; Manish Kumar; Amit Kumar Bhattacharya (Telangana Journal of Psychiatry)
Capgras syndrome is one of the delusional misidentification syndromes, where the patient believes that a familiar person, particularly a loved one, has been replaced by an imposter or a double, and is a rare entity in clinical practice. Although the phenomenon is known to occur as a part of other psychiatric disorders such as schizophrenia and mood disorders, it is not infrequently encountered in organic conditions such as cerebrovascular disease, dementia, and epilepsy. Thus, it is important to rule out any underlying organic etiology by the use of appropriate neuroimaging techniques whenever felt necessary. There are no clear-cut guidelines regarding the treatment of this condition, but atypical antipsychotics seem to be the first-line agents. In this article, we have described three cases, who presented with Capgras syndrome, in association with various other psychiatric diagnoses, such as cannabis-induced psychosis, recurrent depressive disorder, currently severe depressive episode with psychotic symptoms, and schizophrenia. All the cases responded well after treatment with olanzapine, with complete resolution of Capgras delusions in the first two cases, and partial response in the third case, where there was a reduction in the level of conviction of Capgras delusions, and marked improvement in overall functioning. Thus, olanzapine could be a reasonable choice in treating Capgras syndrome in patient populations where there are no contraindications to prescribe this drug.